CASE REPORT IN A PATIENT WITH OSTEOGENESIS IMPERFECTA - Biljana Todorova; Sasha Jovanovska Mishevska; Argjent Mucha; Iskra Bitovska (My University, 2022)
Osteogenesis imperfecta is a genetic disease that is manifested by increased bone fragility, low bone mass and other manifestations of connective tissue. 85-90% are associated with pathogenic variants of the COL1A1 and COL1A2 genes and lead to defects in collagen type 1. Case report: 30-year-old female patient. Diagnosed nanosomia at 5 years old. MRI of the pituitary gland - empty cells, with an ectopic neurohypophysis. At the age of 12, a curvature of the lower legs was observed. She has blue sclerae, a triangular face. Several doses of growth hormone were given due to hypopituitarism. It prevented the occurrence of fractures. In puberty, she got curvature of the lower legs (microfractures or insufficient deposit of calcium in the grown bone due to a mild form of osteogenesis imperfecta type 1). FRACTURES: Condition after a fracture of the right radius in the distal part and the styloid process of the right ulna conservatively resolved with plaster immobilization (2017 year), Fractura et VLC phalangis distalis digiti mani IV lat. dex., Contusio reg. phalangis digiti minimi l. dex.(2015 year), St post conquasatio dig. IV , V manii dex (2015 year), St. post fracturam radii part distalis (2014 year). Positive family history-cousin, nephews of cousin with osteogenesis imperfecta. DXA- Т score on vertebrae=-3.7; on left femur=-0.2; on right femur=-0.4. Discussion: Osteogenesis imperfecta should be considered in patients with frequent fractures. Conclusion: Bisphosphonate treatment reduces fracture rates. New antiresorptive and anabolic agents are being investigated, but the efficacy and safety of these drugs need to be better established.